Efektivitas Metode Demonstrasi dalam Meningkatkan Kemampuan Bercocok Tanam Bawang Daun pada Anak Tunagrahita Ringan - Rahmah Sari Dewi; Jon Efendi (Jurnal Penelitian Pendidikan Khusus, 2022)
Children with mental retardation have low intellectual abilities and abilities compared to children in general. Children with mental retardation can still do simple work although they still need supervision. So that they can be given skills and have life skills and are able to be economically independent. One of the skills that can be given is farming. The school also has a large enough land to be used as a place to grow crops using polybags. Therefore, the researchers conducted an experiment "increasing the ability to grow leek using the demonstration method". The method used is pre-experimental, using a pretest and posttest single group design. The implementation of this research at SLB Kasih Ibu in Pekanbaru with five children with mild mental retardation. Based on the results of the Wilcoxon test in this study, it showed that the ability to cultivate leeks in mild mentally retarded children in class VII students had increased. The conclusion that can be drawn is that the demonstration method can improve the ability to grow leeks in class VII mild mentally retarded children at SLB Kasih Ibu.